2019
DOI: 10.1159/000500146
|View full text |Cite
|
Sign up to set email alerts
|

Development of and Gathering Validity Evidence for a Theoretical Test in Thoracic Ultrasound

Abstract: Background: Thoracic ultrasound (TUS) has a high diagnostic accuracy for many common pulmonary diseases, but theoretic knowledge in sonographic physics, thoracic anatomy and physiology, and sonopathologic patterns is required to develop competence. Objectives: The aims of the study were to develop and gather validity evidence for a theoretical test in TUS and to establish a pass/fail standard. Methods: Content was provided based on expert interviews, leading to creation of 113 initial multiple-choice (MCQ) ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 34 publications
1
26
0
2
Order By: Relevance
“…Several studies assess new operators' theoretical knowledge by using theoretical tests [270][271][272][273]. All studies showed increased knowledge regardless of the learning method used, but only one study presented validity evidence for the theoretical test that was used [274].…”
Section: Trainingmentioning
confidence: 99%
“…Several studies assess new operators' theoretical knowledge by using theoretical tests [270][271][272][273]. All studies showed increased knowledge regardless of the learning method used, but only one study presented validity evidence for the theoretical test that was used [274].…”
Section: Trainingmentioning
confidence: 99%
“…The study did not explore the overall educational strategy in thoracic ultrasound. The content of the theoretical part was identical in all three groups and predetermined based on a Delphi-like method including experts in thoracic ultrasound from different specialties in another study [14]. Physicians from different specialties, departments, or institutions might have different approaches and different educational needs which should be considered in future training programs.…”
Section: Discussionmentioning
confidence: 99%
“…A proposal for future educational training programs could be the following: theoretical session (classroom-based lectures or online web-based education) ending with a theoretical test for ensuring sufficient theoretical knowledge [14]. Practical hands-on training either in a clinical setting, scanning patients without the scanning influencing the patient flow or in a simulated setting scanning healthy volunteers or colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, all test participants had a relatively high level of US experience (equivalent to EFSUMB level I or higher), and thus our lowest proficiency group could be classified as "CEUS-naı ¨ve US intermediates." Several similar studies of theoretical test development within medical education compare test performance of medical students and specialists, which are the two extremes of proficiency level (Jørgensen et al 2019;Pietersen et al 2019). Naturally, when comparing very high and very low proficiency groups, the likelihood of observing a significant difference in test scores is higher, and the probability of false negatives and positives when establishing a pass/fail score is lower.…”
Section: Relationship To Other Variablesmentioning
confidence: 99%